Pembangunan era Desentralisasi: Kedaulatan Ekonomi dan Kelestarian Alam yang Terabaikan - Joko Purnomo (Department of International Relations, Brawijaya University, 2014)
Abstract Decentralizationin Indonesia that took place in the late of 1990s have changed power relations between central and local government. Now local governments have been enjoying significant political and economical powers to manage local affairs. The implementation of development during decentralization that strongly relies on the idea of economic development provides opportunities for global corporations to participate in local development process. As collaborative works between local government and global corporation on the implementation of economic development contribute to the deepening of global corporation into local economic development, they also give significant impacts to the environment as demonstrated by the case of Gunung Tumpang Pitu in Banyuwangi, East Java. It is argued that development without strong awareness on economic sovereignty and environmental protection will lead to environmental degradation and economic fragility. Keywords: Decentralization, development, environment, forestry, global corporations.